(untitled) - Hickmann, Maya (Cambridge,New York, 2003)
Psycholinguist Maya Hickmann presents an original comparative study of discourse development in English, French, German, and Chinese. Hickmann discusses the main theoretical issues in the study of first language acquisition and provides a wide review of available studies in three domains of child language: person, space and time. Her findings concern the rhythm of language acquisition, its formal and functional determinants, and its universal vs. language-specific aspects. The conclusions stress the importance of relating sentence and discourse determinants of acquisition in a crosslinguistic perspective
Keywords: Language acquisition,Discourse analysis, Narrative,Space and time in language,Lý thuyết ngôn ngữ học